Frequency and Causes of Line of Sight Issues During Neurosurgical Procedures Using Optical Image-Guided Systems - Mehbodniya, Amir H.; Moghavvemi, Mahmoud; Narayanan, Vairavan; Waran, Vicknes (Elsevier, 2019)
Background: Navigation (image guidance) is an essential tool in modern neurosurgery, and most surgeons use an optical tracking system. Although the technology is accurate and reliable, one often is confronted by line of sight issues that interrupt the flow of an operation. There has been feedback on the matter, but the actual problem has not been accurately quantified, therefore making this the primary aim of this study. It is particularly important given that robotic technology is gradually making its way into neurosurgery and most of these devices depend on optical navigation when procedures are being conducted. Methods: In this study, the frequency and causes of line of sight issues is assessed using recordings of Navigation probe locations and its synchronised video recordings. Results: The mentioned experiment conducted for a series of 15 neurosurgical operations. This issue occured in all these surgeries except one. Maximum duration of issue presisting reached up to 56% of the navigation usage time. Conclusions: The arrangment of staff and equipment is a key factor in avoiding this issue. © 2018 Elsevier Inc.